PENGEMBANGAN UNIT PENANGKAR BIBIT LADA BERKUALITAS DI POLITEKNIK NEGERI LAMPUNG - Bambang Utoyo; Adryade Reshi Gusta; Yan Sukmawan; Made Same (J-Dinamika : Jurnal Pengabdian Masyarakat, 2018)
Pepper is one of the spice crops that contribute to improving the Indonesian economy. Pepper cultivation is carried out on a small scale to a large scale. Pepper propagation by cutting is considered quite effective and efficient. Politeknik Negeri Lampung has been develop the Pepper Nursery Unit since 2007. This unit runs a business in the production of climbing pepper seedling, shrub pepper seedling, and pepper nursery training. The aim of this program is to support the mission of Politeknik Negeri Lampung in preparing itself to face college campus autonomy through the acquisition of revenue from established business units, accelerating the process of developing an entrepreneurial cultural system in the campus environment, providing competency development opportunities for staff and students, and increasing the role of the Politeknik Negeri Lampung for the community, especially in agriculture. The impact of this program is the availability of hight quality pepper seedling, increasing income generating Politeknik Negeri Lampung, establishment of the Pepper Nursery Unit and training service, improving the skills of Politeknik Negeri Lampung students in pepper nursery, developing entrepreneurial potential for students and staff, as well as increasing the role of Lampung State Polytechnic in community service activities.Keywords—Campus entrepreuneurship, estate crop, nursery business.